The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Rénover la pratique de l’éducation à la sexualité des personnes ayant des incapacités intellectuelles - Dupras, André (Nouvelles pratiques sociales, 2013)
La reconnaissance du droit des personnes ayant des incapacités intellectuelles à une éducation à la sexualité a généré la conception et l’implantation de programmes éducatifs. À quelles valeurs et croyances les professionnels se réfèrent-ils pour organiser l’éducation à la sexualité? Une analyse critique des approches dominantes actuelles est proposée pour contribuer à leur progrès et à leur transformation. Pour dépasser les limites des approches paternalistes et objectivistes, il est suggéré d’adopter un nouveau paradigme fondé sur des perspectives participatives et subjectivistes. Le renouvellement de l’éducation à la sexualité pourrait procéder par énovation en enrichissant et en élargissant les pratiques existantes.
Keywords: amérique du nord; amériques; approches et analyses; canada; capacitisme; discipline; intervention sociale; québec; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle